2002
DOI: 10.1136/ard.61.8.704
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17 induces cartilage collagen breakdown: novel synergistic effects in combination with proinflammatory cytokines

Abstract: Objective: To investigate whether interleukin 17 (IL17), derived specifically from T cells, can promote type II collagen release from cartilage. The ability of IL17 to synergise with other proinflammatory mediators to induce collagen release from cartilage, and what effect anti-inflammatory agents had on this process, was also assessed. Methods: IL17 alone, or in combination with IL1, IL6, oncostatin M (OSM), or tumour necrosis factor α (TNFα), was added to bovine nasal cartilage explant cultures. Proteoglycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
146
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(162 citation statements)
references
References 41 publications
15
146
0
1
Order By: Relevance
“…IL-17 increases the spontaneous production of MMP-1 by synoviocytes (36) and induces MMP-9 production in human monocyte/macrophages (15). In IL-17-treated chondrocytes, expression of mRNA for MMPs 1, 3, and 13 was detected, and a synergistic induction of these MMPs was seen when IL-17 was combined with other proinflammatory cytokines (14). Stimulation of normal human articular chondrocytes with IL-17 was shown to induce nitric oxide production and increase iNOS expression (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17 increases the spontaneous production of MMP-1 by synoviocytes (36) and induces MMP-9 production in human monocyte/macrophages (15). In IL-17-treated chondrocytes, expression of mRNA for MMPs 1, 3, and 13 was detected, and a synergistic induction of these MMPs was seen when IL-17 was combined with other proinflammatory cytokines (14). Stimulation of normal human articular chondrocytes with IL-17 was shown to induce nitric oxide production and increase iNOS expression (37).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that IL-17, acting in synergy with IL-1 or TNF, has powerful effects on cytokine (9,27,28) and chemokine (8) induction and cartilage degradation (14,29). The aggravation of arthri- tis by IL-17 during the first days of SCW-induced arthritis could be caused by additional, or even synergistic, effects of IL-17 in the presence of IL-1 and TNF, both of which are abundantly produced just after the onset of SCW-induced arthritis (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, it inhibits chondrocyte metabolism in intact articular cartilage of mice and results in proteoglycan breakdown (19,20,30,31). Furthermore, in vitro studies show the induction of metalloproteinases by IL-17 in synoviocytes and chondrocytes (32)(33)(34). Interestingly, the effects of IL-17 on matrix degradation and synthesis were not dependent on IL-1␤ production by chondrocytes, and IL-1 receptor antagonist did not block IL-17-induced matrix release nor did it prevent the inhibition of matrix synthesis in vitro using porcine articular cartilage explants (31).…”
Section: Discussionmentioning
confidence: 99%
“…cess by which joint inflammation is suppressed. Previous in vitro and ex vivo studies have shown the great capacity of IL-17 to synergize with TNF-␣ and IL-1 in the induction of other cytokines and chemokines 31,32 and the degradation of cartilage 33,34 and bone. 35 The interaction of IL-17 with other cytokines during reactivation of experimental arthritis, in particular the additive and synergistic effects with TNF-␣ and IL-1, might play an important role in preventing joint pathology.…”
Section: Discussionmentioning
confidence: 99%